Nasal obstruction: relevant surgical aspects - Roithmann, Renato (2022)
This paper reviews essential concepts related to the main anatomical areas associated with the genesis of the nasal obstruction symptom: the nasal valve area, the middlemeatus and the choana/rhynopharynx space.